Stress monitoring using a distributed wireless intelligent sensor system.
We are developing personal health monitors based on a wireless body area network (BAN) of intelligent sensors. Individual monitors will be integrated into a distributed wireless system for synchronized monitoring of a group of subjects. This system could be used during the selection process and as part of a psychophysiological evaluation of military members undergoing intense training. We use measures of heart-rate variability to quantify stress level prior to and during training as well as to predict stress resistance. This task requires reliable, high-precision instrumentation and synchronized measurements from a group of individuals over prolonged periods (days of training).
Keywords: Distributed wireless intelligent sensor system; Heart-rate variability; Intense training; Military members; Personal health monitors; Psychophysiological evaluation; Stress monitoring; Synchronized measurements; Wireless body area network